Tonian (Neoproterozoic) eukaryotic and prokaryotic organic-walled microfossils from the upper Visingsö Group, Sweden. (3rd April 2018) - Loron, Corentin; Moczydłowska, Małgorzata
ABSTRACT: The diversification of protists and multicellular microorganisms is recorded in numerous worldwide Tonian age successions, including the Visingsö Group in Sweden. The Visingsö Group contains a taxonomically rich assemblage of cyanobacteria, stromatolites, algal phytoplankton and vase-shaped microfossils. A new record of organic-walled microfossils from the Visingsö 1 drillcore reveals the high taxonomic diversity. Several species are reported for the first time from the Visingsö Group, and one new species Leiosphaeridia gorda n. sp. is described. They are in gross phycoma-like cysts of the prasinophycean algae Pterospermopsimorpha, Pterospermella, Simia, Macroptycha and Dictyotidium . Morphologically similar to zygotic cysts of chlorophycean algae are Leiosphaeridia gorda n. sp., Cerebrosphaera, Culcitulisphaera and Lanulatisphaera. Schizofusa may represent the earliest yellow-green algae of the Eustigmatiphyte among Stramenopiles. The recorded biodiversity documents the global trend in the evolution of eukaryotic protists during the Tonian Period and the increased radiation of numerous, presumably photoautotrophic biotas, representing various algal lineages.